Synthesis of electronically tunable multifunction biquad filter using voltage differencing differential input buffered amplifiers - Sirigul Bunrueangsak; Winai Jaikla; Amornchai Chaichana; Piya Supavarasuwat; Surapong Siripongdee; Peerawut Suwanjan (My University, 2024)
Abstract Biquad filters are commonly used in analog circuits for various purposes in signal processing and communication applications. We synthesize an analog active biquad filter with five types of voltage‐mode filtering functions. The filter is synthesized using a parallel passive resistor‐inductor‐capacitor (RLC) network and unity‐gain voltage differencing amplifier. A voltage differencing differential input buffered amplifier (VD‐DIBA) is the main active component, and the biquad filter has a three‐input single‐output (TISO) topology. By replacing the passive inductor and resistor with VD‐DIBA‐based inductance and resistance simulators with a subtractor, the TISO voltage‐mode versatile filter is obtained from two VD‐DIBAs, one resistor, and two capacitors connected to the ground. The proposed filter can provide five types of voltage‐mode filtering functions: inverting bandpass and lowpass responses as well as noninverting band‐stop, high‐pass, and all‐pass responses. The all‐pass filter requires no additional active components. The three input voltage nodes have high impedance, and a low‐impedance output voltage node facilitates cascade connections without using additional voltage buffers. In addition, the natural frequency and quality factor can be electronically tuned. The quality factor is controlled without disturbing the passband gain and natural frequency. The proposed filter is simulated and verified experimentally in the Personal Simulation Program with Integrated Circuit Emphasis (PSPICE) and through laboratory tests employing VD‐DIBAs implemented using commercially available components.
Keywords: Digital biquad filter; Analog and Mixed-Signal Circuit Design